The use of occupation-based intervention among Malaysian occupational therapists: a focus group discussion - Ahmad, Aisyah; A. Rahman, Padma; Tomori, Kounosuke; Wan Yunus, Farahiyah; Romli, Muhammad Hibatullah; Che Daud, Ahmad Zamir (Informa UK Ltd, 2022)
Research regarding occupation-based intervention (OBI) has been mainly conducted in developed Western and Asian countries. Therefore, the transferability and generalisability of the published research to the Malaysian context is questionable. The purpose of this study was to examine Malaysian occupational therapists’ perceptions of the developed definition of OBI and how they put it into practice. Three focus group discussions were conducted. Participants were recruited among Malaysian occupation-based practitioners. Data were analysed using a manifest and latent content analysis. The major finding that emerged from the data analysis was the practice of OBI in Malaysia, which was further divided into how OBI is implemented in Malaysia, and the facilitators to practise OBI. This study’s findings suggest that OBI was implemented in various ways by the Malaysian occupational therapists despite agreeing with the developed definition of OBI as occupation as a means and an end.